Relações semântico-lexicais e a coesão textual: contribuições para o ensino da escrita - Miranda, Alessandra Magda de (2014)
Due to discussions about the relationship between the textual-discursive theories and the daily practice of Portuguese language teaching, this paper tries to reflect on the importance/relevance of the knowledge of the semantic-lexical relations for the creation of texts, thus highlighting the need for the Portuguese language teachers contemplate, in their classes, activities which include the study of the lexicon, especially when working with writing. Therefore, we supposed that: 1) Great part of the problems in textual cohesion, verified in High School students written texts, have been justified due to the absence of classroom activities which contemplate/explore the several relations of meaning established between the lexical units and their function in the textual architecture; 2) If activities which include the study of lexicon, as an essential element for text organization, are suitable approached in the teaching and learning process of the native language, students will be able to present better results when working with writing. Aiming to confirm, or maybe not, these hypotheses, we have chosen, as research locus, two groups from E.E.E.F.M. CAIC José Joffily, a public school in the city of Campina Grande, Paraiba, where we work as a Portuguese teacher and we proposed to: verify the importance of the lexical knowledge to textual cohesion; check the possibility of working the study of lexical relations connected to the work of text production in the classroom; present the results of the contribution of the lexical knowledge to text production through the comparative analysis of the texts produced by the students before and after the activities which include the study of the lexicon. Therefore, we have adopted the didactic sequence procedure as a didactic-methodological tool, according to Dolz, Noverraz and Schneuwly (2004). So, our study is a qualitative research which has been developed by means of an action research based on the theoretical assumptions of Semantics and Applied Linguistics. The analyses undertaken during this study have confirmed the motivating hypotheses of the research and confirm the relevance of implementing activities which include the study of the lexicon associated with the teaching of writing.